The infiltration behavior and chemical compatibility of molten lead-bismuth eutectic in nuclear graphite at elevated temperature - He, Z; Liu, Z; Marrow, TJ; Song, J (Elsevier, 2021)
Six grades of commercial nuclear graphite of different microstructures (NBG-17, NBG-18, NBG-25, IG-110, NGCT-50 and ZXF-5Q) were infiltrated with molten lead-bismuth eutectic (LBE) at 800°C and a series of pressures to evaluate their barrier property to molten LBE. Molten LBE infiltration caused a decrease of the (002) interlayer spacing and an increase of mean crystallite dimension perpendicular to the (002) diffracting plane. This is ascribed to compressive stress evolution from the infiltration and subsequent solid-state phase transformation of LBE. One representative graphite (IG-110) was immersed in molten LBE at 800°C for 1000 hours and no evidence of corrosion was detected, which has preliminarily verified the chemical stability of graphite in molten LBE. This work indicates that nuclear graphite with small pores has great chance to act as coolant channel material for compact high temperature reactor.